Origami científico: a linguagem das dobraduras dentro do design contemporâneo - Teixeira, Samanta Aline; Rossi, Dorival Campos [UNESP] (My University, 2013)
After crossing several generations and countries, broader functions are being incorporated to origami than simply making art objects: the fold initiates a series of new buildings within the design and creation. Under the new repre- sentations and performances that the art of paper folding keeps, this article aims to investigate how the origami is configured nowadays and how it behaves while contemporary language applied to projective processes of diverse natures. To better understand the actual origami, relations are used inside branch of math, conceptual and projectual. Relating theorists, artists, designers, etc., can point out the relevance of each of these areas in the configuration of cientific and projectual origami. The modularity, the collective, the conscious build, the contemporary and the inno- vation are relationships intrinsic to the praxis projectual that shape a landscape adjacent and subordinate to the main structure governing. It bets on the essence of origami as a tangible functionality for creative thinking.

Depois de atravessar inúmeras gerações e países, funções mais abrangentes estão sendo incorporadas ao origami além da simples confecção de objetos artísticos: o dobrar vêm desencadeando uma série de novas construções dentro do projeto e da criação. Sob as novas representações e atuações que a arte de dobrar papel encerra, esse artigo se propõe a investigar como o origami se configura nos dias de hoje e como se comporta enquanto linguagem contemporânea aplicada aos processos projetuais das mais diversas naturezas. Relacionando teóricos, artistas, designers, etc, pode-se apontar a relevância de cada uma dessas áreas na configuração do origami científico e projetual. A modularidade, o coletivo, o construir consciente, o contemporâneo e a inovação são relações intrínsecas à práxis projetual que configuram um panorama adjacente e subordinado à estrutura principal que regem este projeto de pesquisa. Apostamos na essência do origami como uma funcionalidade tangível para o pensamento criativo.
Keywords: Origami; Design; Processes; Transdisciplinarity; Innovation; Origami; Design; Processos; Transdisciplinaridade; Inovação